2019
DOI: 10.1504/ijgw.2019.10021851
|View full text |Cite
|
Sign up to set email alerts
|

A framework for predicting the effects of climate change on the annual distribution of Lyme borreliosis incidences

Abstract: Global climate change is predicted to affect both the spatial and annual distributions of vector-borne diseases. Tick-borne diseases are particularly sensitive to the changing climatic conditions. Modeling them is, however, challenging due to the input-intensity of these models. A framework with low number of inputs (easily accessible weekly temperature data and week numbers) on modeling the seasonality of Lyme borreliosis incidences is presented. The modelling framework enables predicting the annual distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Our study has shown that the transmission potential and the risk in the study site are expected to increase as well as the chance of transmission by co-feeding ticks. The extended length of tick season in Hungary is expected in the study [27]. Several other studies have also assessed the impact of climate change on the activities of ticks and the spread of tick-borne diseases [27][28][29][30][31], addressing the importance of the proactive action plans against the changing risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown that the transmission potential and the risk in the study site are expected to increase as well as the chance of transmission by co-feeding ticks. The extended length of tick season in Hungary is expected in the study [27]. Several other studies have also assessed the impact of climate change on the activities of ticks and the spread of tick-borne diseases [27][28][29][30][31], addressing the importance of the proactive action plans against the changing risk.…”
Section: Discussionmentioning
confidence: 99%
“…These shifts could instigate interactions with other taxa, possibly disrupting established community dynamics. Altitudinal displacement has also been observed in or predicted for other Mediterranean trees and endemic or rangerestricted species [15,53,108,[126][127][128][129][130][131], which may lead to the reshuffling of high-altitude forest composition and a change in dominant trees, with alpine conifers potentially substituted by oaks and Mediterranean pines [132,133]. This phenomenon, in turn, may alter the provision of ecosystem services in high mountain forests [134].…”
Section: Habitat Suitability Range Change and Iucn Extinction Risk As...mentioning
confidence: 99%
“…The Mediterranean Basin, recognised both as a global biodiversity hotspot [4] and a climate change hotspot [5,6], epitomises these challenges. It has already manifested ecological shifts, including phenological alterations [7], reduced provision of regulating ecosystem services [8], and species loss [9][10][11][12][13][14], with these alterations predicted to intensify, especially in Mediterranean forests [8,15,16]. Conversely, land-use modification has emerged as a primary factor in plant extinctions over recent centuries [17], significantly transforming continental Europe's vegetation [18] and causing excessive soil erosion in Mediterranean forests [5].…”
Section: Introductionmentioning
confidence: 99%